2023
DOI: 10.1017/s0031182023000689
|View full text |Cite
|
Sign up to set email alerts
|

Predicting climate-driven distribution shifts in Hyalomma marginatum (Ixodidae)

Abstract: Hyalomma marginatum is an important tick species which is the main vector of Crimean–Congo haemorrhagic fever and spotted fever. The species is predominantly distributed in parts of southern Europe, North Africa and West Asia. However, due to ongoing climate change and increasing reports of H. marginatum in central and northern Europe, the expansion of this range poses a potential future risk. In this study, an ecological niche modelling approach to model the current and future climatic suitability of H. margi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 105 publications
(162 reference statements)
0
0
0
Order By: Relevance
“…Predicting the distribution of H. marginatum (the presumed main vector) is of great importance for identifying future health risks. Recent studies suggested that H. marginatum will remain in areas where it is currently distributed and will also expand to new areas where it has not been reported before [224]. Likewise, the progress of tick-borne encephalitis and Lyme borreliosis should be carefully monitored, as these diseases are not currently reported in Turkey but constitute a potential threat due to the presence of their tick vector.…”
Section: Turkeymentioning
confidence: 99%
“…Predicting the distribution of H. marginatum (the presumed main vector) is of great importance for identifying future health risks. Recent studies suggested that H. marginatum will remain in areas where it is currently distributed and will also expand to new areas where it has not been reported before [224]. Likewise, the progress of tick-borne encephalitis and Lyme borreliosis should be carefully monitored, as these diseases are not currently reported in Turkey but constitute a potential threat due to the presence of their tick vector.…”
Section: Turkeymentioning
confidence: 99%